1993
DOI: 10.1126/science.7694366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the EGF-Activated MAP Kinase Signaling Pathway by Adenosine 3′,5′-Monophosphate

Abstract: Mitogen-activated protein (MAP) kinases p42mapk and p44mapk are activated in cells stimulated with epidermal growth factor (EGF) and other agents. A principal pathway for MAP kinase (MAPK) activation by EGF consists of sequential activations of the guanine nucleotide exchange factor Sos, the guanosine triphosphate binding protein Ras, and the protein kinases Raf-1, MAPK kinase (MKK), and MAPK. Because adenosine 3',5'-monophosphate (cAMP) does not activate MAPK and has some opposing physiologic effects, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
646
8
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(707 citation statements)
references
References 33 publications
46
646
8
3
Order By: Relevance
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…However, it should be noted here that G s stimulates proliferation only in the cells ± such as those present in endocrine tissues ± that are positively responsive to cAMP-PKA signaling pathway for their cell growth. By contrast, in other cells, Ga s appears to have a growth inhibitory e ect through its negative regulation of Ras-Raf signaling pathway (Burgering et al, 1993;Graves et al, 1993;Cook and McCormick, 1993;Wu et al, 1993;Sevetson et al, 1993). In these cell types, PKA activated by Ga s through cAMP directly phosphorylates Raf at Ser 43 and/or Ser 671 Mischak et al, 1996) thus inhibiting Raf and its downstrean MEK-ERK cascade.…”
Section: Ga S and The Gsp Oncogenementioning
confidence: 99%
“…A case to the point is the ability of cAMP from G s signaling pathway to inhibit ERK-signaling pathway (Burgering et al, 1993;Graves et al, 1993;Cook and McCormick, 1993;Wu et al, 1993;Sevetson et al, 1993). Recently it has been shown that during genotoxic stress, p53, the well characterized tumor suppressor, downregulates the activity of Ga q and Ga 11 through Ga q/11 -speci®c RGS protein (Buckbinder et al, 1997), a negative regulator of G protein activity (Berman and Gilman, 1998).…”
Section: G Protein Interactions With Other Signaling Pathwaysmentioning
confidence: 99%
“…It has been shown that PKA directly regulates the ras signaling pathway by phosphorylating raf-1 kinase (Wu et al, 1993;Cook and McCormick, 1993) and that the activated a-subunit of the heterotrimeric guanine nucleotide binding protein inhibits proliferative signals from ras through cAMP and PKA (Chen and Iyengar, 1994). In these mechanisms of action, an increase in intracellular cAMP levels is an essential prerequisite.…”
mentioning
confidence: 99%